Valproate-Induced Pubertal Arrest - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
A 12-year-old girl with complex partial seizures who had pubertal arrest of both growth and secondary sexual development while receiving VPA is reported from the Department of Pediatrics, Wright State University, Dayton, OH and the University of Iowa, Iowa City, IA.